Design and evaluation of a prototype medical device for robotic and manual percutaneous dilatational tracheostomy - Yuan Tang; Glen Cooper; Damian Crosby; Brendan A. McGrath; Andrew Weightman (PLoS ONE, 2026)
Percutaneous Dilatational Tracheostomy (PDT) is frequently performed at the intensive care unit bedside. Perioperative movements of instruments, especially inserting and removing the needle and dilators, may cause severe complications in around 10% of total patients. This research aims to reduce the complications associated with PDT instruments and simplify the procedure by proposing a prototype medical device called TrachyPen. Either used robotically or manually, TrachyPen combined the PDT puncture and dilation into a single step to eliminate the use of multiple instruments and their complex operations. Considering the insertion and dilation force as a critical safety factor for PDT, fifty simulated PDT insertion and dilation experiments were conducted on porcine back skins to evaluate the force profiles of TrachyPen and compare them with the Ciaglia Blue Rhino (CBR) dilator, commonly used in current clinical practice. Results illustrated a smaller stoma of 13.67(164) mm and a smaller insertion force of 53.45(807) N by TrachyPen compared with CBR (16.17(205) mm and 69.01(842) N). This research proves the concept of the TrachyPen design and the potential of using it for robotic PDT puncture and dilation.